PERLINDUNGAN ANAK KORBAN PERCERAIAN DI LINGKUNGAN PESANTREN: ANALISIS SOCIO-LEGAL DALAM PERSPEKTIF HUKUM ISLAM, HUKUM POSITIF DAN PSIKOSOSIAL - Alfindo Fernanda Risqi; Leliya; Samsudin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the protection of children affected by parental divorce in Islamic boarding school (pesantren) environments through a socio-legal approach that integrates Islamic law, Indonesian positive law, and psychosocial perspectives. The research is motivated by the gap between comprehensive legal norms governing child protection and empirical realities, which show that their implementation remains largely formalistic and has not fully addressed children’s psychosocial needs. This study employs a qualitative method with a normative-empirical approach. Data were collected through in-depth interviews, participatory observation, and documentation at Pesantren Sains Salman Assalam Cirebon, involving students from divorced families, caregivers, dorm supervisors, and parents. The findings indicate that children of divorced parents experience psychosocial impacts such as emotional disturbances, difficulties in social adaptation, reduced self-confidence, and spiritual challenges. Nevertheless, pesantren play an important role in building children’s resilience through collective caregiving, social support, emotional mentoring, and religious practices that function as religious coping mechanisms. The study also identifies a gap between legal norms and their implementation, particularly in post-divorce child support monitoring and psychosocial assistance services. In conclusion, the protection of children affected by divorce requires a more holistic and integrated approach that goes beyond legal certainty and emphasizes psychological and social recovery through the involvement of community-based institutions such as pesantren.